2006
DOI: 10.1016/j.jhealeco.2005.12.005
|View full text |Cite
|
Sign up to set email alerts
|

SCHIP expansion and parental coverage: An evaluation of Wisconsin's BadgerCare

Abstract: The Wisconsin BadgerCare program, which became operational in July 1999, expanded public health insurance eligibility to both parents and children in families with incomes below 185 percent of the U.S poverty line (200 percent for those already enrolled). This eligibility expansion was part of a federal initiative known as the State Children's Health Insurance Program (SCHIP). Wisconsin was one of only four states that initially expanded coverage to parents of eligible children. In this paper, we attempt to We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“… 4. Although employment information is available in CARES, Wolfe et al (2006) found it to be of very low quality relative to UI information. Thus, we do not use employment information from CARES.…”
mentioning
confidence: 99%
“… 4. Although employment information is available in CARES, Wolfe et al (2006) found it to be of very low quality relative to UI information. Thus, we do not use employment information from CARES.…”
mentioning
confidence: 99%
“…All low to moderate-income families, with a child under the age of 19, who do not qualify for Medicaid in Wisconsin are eligible for BadgerCare. It has been estimated that BadgerCare increased the public healthcare coverage of all adults previously receiving cash assistance from Aid to Families with Dependent Children (AFDC) or Temporary Assistance for Needy Families (TANF) by about 17-25% points (Wolfe et al 2006). Several studies have reported that SCHIP expansion in coverage reduced the likelihood that a parent will report forgoing needed medical care due to cost and an increased utilization of preventative care (Buchmueller et al 2005; Busch and Duchovny 2005; Guendelman et al 2006; Yu et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Most W-2 participants qualified for Medicaid, but New Hope’s advantage was that it provided affordable health care regardless of welfare or family status, either through HMOs used by Medicaid or through supplementing payments for employer-based insurance (Huston et al, 2003). By 1999, Wisconsin had created BadgerCare, which offered medical insurance to uninsured families with children whose incomes were less than 185 percent of the FPL (200 percent of FPL for continuing enrollees; Wolfe et al, 2006). …”
Section: The New Hope Projectmentioning
confidence: 99%